2008
DOI: 10.1016/j.tetlet.2008.08.052
|View full text |Cite
|
Sign up to set email alerts
|

A new antimalarial polyether from a marine Streptomyces sp. H668

Abstract: The antimalarial guided fractionation of the culture of marine Streptomyces sp. strain H668 led to the isolation of a new polyether metabolite. The structure was determined by comprehensive NMR and MS assignments. This new metabolite showed in vitro antimalarial activity against both the chloroquine-susceptible (D6) and -resistant (W2) clones of Plasmodium falciparum, without cytotoxicity to normal cells (Vero) making it a promising first lead from this marine bacterium.Malaria is a tropical infection caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…A polyether isolated from the marine Streptomyces sp. H-668 and named hawaiimycin-I (34) ( Figure 1) [ 48 ] reinforced the critical role of certain key structural features including the terminal carboxylic group on the bioactivity of carboxyl ionophores. Hawaiimycin-I (34) is extremely close structurally to a set of carboxyl ionophores reported as potent antimalarial [ 40 ,44], that is, monensin A (1), K-41 (33), nigericin (5), lonomycin (17) and grisorixin (16).…”
Section: Plasmodium Sp-mentioning
confidence: 93%
“…A polyether isolated from the marine Streptomyces sp. H-668 and named hawaiimycin-I (34) ( Figure 1) [ 48 ] reinforced the critical role of certain key structural features including the terminal carboxylic group on the bioactivity of carboxyl ionophores. Hawaiimycin-I (34) is extremely close structurally to a set of carboxyl ionophores reported as potent antimalarial [ 40 ,44], that is, monensin A (1), K-41 (33), nigericin (5), lonomycin (17) and grisorixin (16).…”
Section: Plasmodium Sp-mentioning
confidence: 93%
“…CRIF1 isolated from a Thai soft coral, was moderately antiplasmodial (IC 50 =1-10 μM) against chloroquine-resistant P. falciparum strain 94. Na et al (2008) identified a new marine Streptomyces sp. H668 polyether (51) from Hawaii that showed in vitro antimalarial activity (IC 50 =0.1-0.2 μg/mL) against both P. falciparum chloroquine-susceptible (D6) and -resistant (W2) clones, with minimal cytotoxicity towards mammalian cells.…”
Section: Antimalarial Antiprotozoal and Antituberculosis Activitymentioning
confidence: 99%
“…H668, exhibited a significant in vitro antimalarial activity (IC 50 ~ 150 ng/mL), with a good selectivity [84]. Some examples of non-marine antimalarial polyether compounds are also present in the literature [85].…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%